Investigating the use and effectiveness of diverse types of materials in the delivery and support of lab sessions for multimedia subjects and students. (27th June 2012) - Tsekleves, Emmanuel; Aggoun, Amar; Cosmas, John
Abstract: This research study explores the use of different lab material, investigating which types of materials contribute the most to the delivery and support of laboratory (lab) sessions to design, skill‐based and technical courses in higher education in the UK. A qualitative research methodology was employed for this investigation and included both key stakeholders in academia, including 75 students and 12 tutors. An investigation was also conducted tracking student activity on the university's e‐learning facility (U‐link). Our key findings indicate that overall electronic material is considered the most effective type of material for the delivery of a lab session. This is followed by print, video and lastly audio material according to student responses and video, print and audio material according to tutor responses. Student and tutor responses varied per individual module/subject area. Video material was regarded by students and tutors as the most effective type for the delivery of skill‐based lab sessions and generally for independent learning, and electronic material was regarded as the most effective type for the delivery of technical and design lab sessions. Lastly, student tracking revealed that the introduction of video lab material in two modules increased the average time spent by students on U‐link by 58% for the technical module and 97% for the skill‐based module respectively.